Resident encounters with disruptive workplace behaviours in Japan: findings from a national cross-sectional study - Ashwin Gupta; Yasuharu Tokuda; Takashi Watari; Yuji Nishizaki; Virginia Sheffield; Kaori Taniguchi (BMJ Open Quality)
Importance Disruptive workplace behaviours (DWBs) between healthcare professionals compromise patient care quality and organisational culture, impacting staff morale, communication and teamwork. Residents are particularly vulnerable to it from nurses and supervisors.Objective Elucidate factors associated with DWBs experienced by residents.Design Nationwide cross-sectional study using a web-based survey.Setting Japanese postgraduate clinical training hospitals.Participants First- and second-year postgraduate residents were surveyed between 15 and 31 January 2023, immediately after participating in the nationally administered computer-based residency exam.Exposure None.Main outcomes and measures Primary outcomes include previously published eight types of DWBs experienced by residents. Resident characteristics at the time of the study were used. Hospital data (location of the training hospital, number of beds, number of emergency transports, average length of hospital stays, number of outpatients per day and the actual number of residents, full-time physicians and nurses) were obtained from Japan’s largest hospital information database.Results Of 5403 residents analysed, 68.3% were males, and 84.9% were under 28 years of age. Residents reported encountering DWBs from physicians and nurses approximately 35% of the time, a roughly equivalent percentage from both groups. After multivariate logistic regression analysis, the likelihood of encountering DWBs from nurses increased with hospital size (>700 beds; adjusted OR (aOR) 2.19; 501–700 beds; aOR 1.45 and 301–500 beds; aOR 1.26, all statistically significant). Furthermore, DWBs from nurses were significantly more prevalent in settings with higher admissions per nurse (aOR 1.70). DWBs from physicians were significantly more prevalent towards male (vs female) residents (aOR 1.60) and less likely among the second-year postgraduate (vs first-year postgraduate) residents (aOR 0.87).Conclusions DWBs from nurses are significantly more common with increasing hospital bed numbers and increase with the number of admissions per nurse. No such correlation was observed with DWBs from physicians. Male residents experience more DWBs than female residents.